Design And Construction of Simpang Empat Village Public E-Service Using Mobile-Based Extreme Programming Method - Zoelkifli, Mayang Zahra; Samsudin, S; Santoso, Heri (IJISTECH (International Journal of Information System and Technology), 2025)
The E-Community Services application is a website and Android-based application that can be used to overcome several problems in community affairs in the Simpang Empat Village government. Some of the matters that can be handled using this application are Single NA Management Letters, Divorce/Death NA Management Letters, Business License Letters and various other letters. This E-Community Services application also provides security and infrastructure features for the community. The type of research used by the author in this research is Qualitative Research and the System Development Method used is the Extreme Programing (XP) method. With data collection techniques consisting of Observation, Interviews and Literature Study. The E-Community Services application that was built has succeeded in helping to overcome various problems in the Simpang Empat Village government. The results of system testing also obtained very good results, so it can be concluded that the system is running well according to the results of the testing and validation that has been carried out.